Obesity association with antidiabetic drugs' prescription among patients with type 2 diabetes mellitus: a systematic review and meta-analysis. (1st April 2022) - Mahmoud, F; Mullen, A; Yasin, H; Abutheraa, N; Kurdi, A
Abstract: Introduction: Type 2 diabetes mellitus (T2DM) is a chronic disease of persistent elevation in blood glucose level. Several antidiabetic drugs (ADDs) with different features are currently available for T2DM management (1). The selection of appropriate ADDs is crucial for preventing/attenuating diabetes-related complications(1). All guidelines agreed on metformin to be an initial therapy for patients diagnosed with T2DM, yet the selection of an intensifying therapy or alternative initial therapy are lacking any agreements (1). Consequently, the selection of ADDs could be linked to multiple factors (2). Since obesity is a risk factor for T2DM and ADDs have variable effect on body weight, obesity is an important factor that could be associated with ADDs' selection. Aim: This systematic review (SR) and meta-analysis (MA) aimed to overview and quantify obesity association with the selection of ADDs among type 2 diabetic patients. Methods: A systematic literature search was conducted on multiple databases. Eligible studies were selected based on the following inclusion criteria: quantitative observational studies, evaluated obesity association with ADDs' prescription, in outpatient setting, and published in English over the period of Jan/2009-April/2021. Studies on other types of diabetes, about switching therapy, or published before 2009 were excluded. The following items were extracted from identified articles: study details as author, year, and method, participants' characteristics as age and gender, type of investigated ADDs, comparison group, and stage of treatment, as well as type of analysis test. Extracted data was synthesized quantitively utilising a three-level MA approach as some studies reported more than one effect-size because of examining multiple ADDs. It was based on odds ratio and 95%confidence interval. Results: A total of 21 studies evaluated the association of obesity with ADDs' prescription was identified. All except one were included in the MA which contributed to a total of 66 effect sizes from all investigated ADDs. The pooled estimate of obesity association with the prescription of ADDs including all groups was 1.19[0.85 -1.67]. A subgroup analysis showed a significant difference according to the type of ADDs (p< .0001). A positive significant association was found with glucagon-Like peptide receptor agonist (GLP1-RA), sodium glucose transporter 2 inhibitors (SGLT2-I), and metformin prescriptions (pooled estimate: 2.35 [1.54-3.59], 1.89[1.33-2.68], and 1.22[1.08-1.37], respectively). Whereas a negative significant association was found with sulfonylurea prescription (pooled estimate: 0.76 [0.62-0.93]). The pooled estimate of thiazolidinedione, dipeptidyl-peptidase 4 inhibitors, and insulin showed a non-significant association with obesity. None of the investigated variables showed significant influence on the overall result including stage of treatment and quality of study (p >0.05). Conclusion: Obesity is an important factor influencing ADDs' prescription. Patients with higher weight were more likely to get ADDs with weight losing or neutral effect as GLP1-RA, SGLT2-I, and metformin. This reflects some adherence of clinical practice to the variability in drugs' features as indicated from the consistent findings of obesity as a factor affecting ADDs' selection with the weight effect of ADDs. Yet, further studies are required because of limited number of studies examined each antidiabetic group. References: 1. American Diabetes A. 9. Pharmacologic Approaches to Glycemic Treatment: Standards of Medical Care in Diabetes-2020. Diabetes Care. 2020;43(Suppl 1):S98-S110. 2. Wilkinson S, Douglas I, Stirnadel-Farrant H, Fogarty D, Pokrajac A, Smeeth L, et al. Changing use of antidiabetic drugs in the UK: trends in prescribing 2000-2017. BMJ Open. 2018;8(7):e022768.